TEORI BELAJAR KOGNITIF DAN IMPLEMENTASINYA PADA PEMBELAJARAN PAI - Bukhari Bukhari (AZKIA : Jurnal Aktualisasi Pendidikan Islam, 2019)
Learning is a conscious effort that can change a person's behavior for the better. Change is not only related to the addition of knowledge but also in the form of skills, skills, attitudes, understanding, self-esteem, interests, character and adjustment. The clarity concerns all aspects of a person's organism and personal behavior. Therefore, learning can be said as a series of mental, psycho-physical activities towards the full development of the human person concerning the elements of creativity, taste and intention, the cognitive, affective and psychomotor domains. In the Islamic perspective, it is described that learning is lifelong, from the cradle to the grave. Become a motivator for students to improve their lives and to achieve noble degrees. The learning process will run smoothly and easily if the principles are applied correctly. Education as a conscious and planned effort shows that education is a deliberate and well thought out process (intellectual work process). Implementation of Gestalt theory in learning, among others: Insightful learning is observation and sudden understanding of the relationships between parts in a problem situation, Meaningful learning is meaningful learning is to give an idea that learning is an effort made in order to gain knowledge and then apply it the purpose of learning is to change the behavior of students for the better. For this reason, in the learning process there must be good planning so that it is able to identify changes in student behavior according to the demands of the times, while transfer in learning is the process of transferring knowledge from educators to students.